2015
DOI: 10.1002/acr.22518
|View full text |Cite
|
Sign up to set email alerts
|

What Do People With Knee or Hip Osteoarthritis Need to Know? An International Consensus List of Essential Statements for Osteoarthritis

Abstract: Objective. To establish priority key messages for patients with osteoarthritis (OA). Methods. A Delphi survey and priority pairwise ranking activity was conducted. Participants included 51 OA experts from 13 countries and 9 patients (consumers) living with hip and/or knee OA. During 3 Delphi rounds, the panel of experts and consumers rated recommendations extracted from clinical guidelines and provided additional statements they considered important. When ‡70% of panel members agreed a statement was "essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
47
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 27 publications
8
47
0
1
Order By: Relevance
“…This need is in concordance with the guideline recommendation that self‐management is important for patients with hip or knee OA . It is also in line with the nature of the key messages that French et al reported to be essential for hip or knee OA patients, because 15 of those 21 statements covered treatment options and management in which the patients have an active role. This concordance between patients and health care professionals provides a good starting point for education and communication about treatment options.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This need is in concordance with the guideline recommendation that self‐management is important for patients with hip or knee OA . It is also in line with the nature of the key messages that French et al reported to be essential for hip or knee OA patients, because 15 of those 21 statements covered treatment options and management in which the patients have an active role. This concordance between patients and health care professionals provides a good starting point for education and communication about treatment options.…”
Section: Discussionsupporting
confidence: 71%
“…In a recent study, French et al used a multistage consensus process to identify key messages that are essential for patients to know, extracted from multiple guidelines about OA. After optimizing the wording of the key messages, an overall ranking of the messages averaged across all panel members was determined.…”
Section: Introductionmentioning
confidence: 99%
“…A standard eDelphi approach consisting of 3 rounds was used to iteratively seek consensus on the draft framework. The methods underpinning the eDelphi were consistent with recent reports . An international panel that consisted of SMEs from phase 1, as well as additional SMEs invited by the Global Alliance for Musculoskeletal Health of the Bone and Joint Decade, was established.…”
Section: Methodsmentioning
confidence: 88%
“…along with tiredness and rigidity, with time, it is more and more difficult to mobilize for motion, and additional activity is inhibited and limited to a necessary minimum. Pain is, thus, the key determinant of the kinesiphobia that leads to sedentary lifestyles and decreased general efficiency, as well as to an increase of the risk of obesity and cardiovascular diseases [10]. a vicious cycle is, thus, created: on the one hand, lack of activity; on the other hand, progress of the disease, resulting in increasing loss of the joint motion extent and the intensifying of pain.…”
Section: C) Disturbed Blood Distribution and Joint Nourishingmentioning
confidence: 99%
“…the 21 recommendations developed by the dElPHi discussion panel (represented by experts in rheumatology, orthopaedics and physiotherapy, as well as by patients themselves) indicated, among other issues, that physical activity and loss of body mass are priority preservative actions in this extent. moreover, regular physical activity and individual exercise programs (including muscle strengthening, cardiovascular activity and flexibility exercises) bring about real chances to lower the pain, decrease the progress of the joint degenerative disorder and improve performance of daily functions [10].…”
mentioning
confidence: 99%